PENGEMBANGAN LAYANAN WEB SPASIAL INFORMASI PEMANFAATAN PENGINDERAAN JAUH - Sarno, Sarno (Institut Teknologi Sepuluh Nopember, 2017)
Dissemination implementation of remote sensing application information through the management of National Earth Observation System at the Remote Sensing Application Center of National Institute of Aeronautics and Space could be achieved by expanding and completing the dissemination mechanism, from the traditional way to spatial web services. The service is a standard defined by the Open Geospatial Consortium. These standards are widely used for the dissemination of spatial information through Web Map Services, Web Feature Services and Web Coverage Services - based standards and greatly assist in the implementation function of data application and remote sensing information dissemination. This research aims to analyze and provide development methods of spatial web services for remote sensing application information. The research methods include setting the initial requirements, programming a map file and spatial web services testing. The results showed that the spatial web services based on University of Minnesota Mapserver has been successfully implemented and tested using Google Map real web map service client and QGIS Desktop in case study forest cover change in Indonesia.